2000
DOI: 10.1017/s0266462300101102
|View full text |Cite
|
Sign up to set email alerts
|

Health Technology Assessment in Italy

Abstract: Italy has a national health service (SSN) dating to 1978. Italy's system of government is characterized by a rather high degree of decentralization of power, and the health system is likewise decentralized. Most of the responsibilities for health care have been ceded to the regions. The state retains only limited coordinating and supervisory powers. The state has a financial responsibility for the national health service, but state contributions are limited and expenditures in excess of this made by the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…During past decades, health care systems of industrialized countries have focussed on the problem of assuring health services to all citizens while reducing the allocation of economic resources (Fleurette and Banta, 2000;France, 2000;Granados et al, 2000;Perlett and Busse, 2000;Jorgensen and Hvenegaard, 2000).…”
Section: Origins Of Health Technology Assessmentmentioning
confidence: 99%
“…During past decades, health care systems of industrialized countries have focussed on the problem of assuring health services to all citizens while reducing the allocation of economic resources (Fleurette and Banta, 2000;France, 2000;Granados et al, 2000;Perlett and Busse, 2000;Jorgensen and Hvenegaard, 2000).…”
Section: Origins Of Health Technology Assessmentmentioning
confidence: 99%
“…Although health technology assessment has expanded considerably since the early 1990s, this activity still tends to be unfocused, uncoordinated and to lack clearly defined priorities [40].…”
Section: Appropriateness Of Carementioning
confidence: 99%
“…Within EU context, limited number of studies analysed the role of HTA in decentralised systems and showed that increasing autonomy assigned to the lower levels of government usually fosters the development of HTA programmes and activities at the regional level leaving the role of national level HTA bodies rather ambiguous [11][12][13][14][15][16]. In all the studies, regional models usually appear to be very different among them in terms of organization, institutional framework, stakeholders and aims.…”
Section: Introductionmentioning
confidence: 99%
“…In all the studies, regional models usually appear to be very different among them in terms of organization, institutional framework, stakeholders and aims. This heterogeneity is argued to be due not only to the different stages of implementation but also to different perception of the role of HTA within the context of the Regional Health Services [11,12]. Consequently, the results of HTA activities across regions can be profoundly different thus generating concern on national issues such as equity of access to healthcare technologies.…”
Section: Introductionmentioning
confidence: 99%